Calculation stress and strain on the edges, rolled bands and strips - Сатонин, Александр Владимирович; Коренко, Марина Георгиевна; Сухоруков, Иван Сергеевич (Eastern-European Journal of Enterprise Technologies, 2011)
Taking into account the real nature of the distributions of boundary conditions on the basis of numerical of recurrence solutions the of finite-difference form of static equilibrium conditions selected elementary volumes of specify methods for calculating the stress-strain state of the metal on the side edges ribbons and bands that are mill